Excavation at Bakr Awa 2010 and 2011 - Miglus, Peter A.; Bürger, Ulrike; Fetner, Rafał A.; Mühl, Simone; Sollee, Alexander E. (Iraq, 2014)
The site of Bakr Awa is situated in north-eastern Iraq, in the Plain of Shahrizor. Excavations were undertaken in 1960/61by the Iraqi Department of Antiquities and 2010/11 by the University of Heidelberg/Germany. Occupation layers from the beginning of the Early Bronze Age tothe Ottoman period were uncoveredin the lower city and on the citadel. Archaeological evidence from the secondmillennium B.C. shows the most intensive settlement activities and apparent prosperity at Bakr Awa. Several forms of pottery, small finds and architecture reflect dynamic processes of cultural and political transformation at this site located in an area of transition between northern and southern Mesopotamia and western Iran.